Effects Of Antenatal Nursing Interventions Based on World Health Organization Module on Fear of Childbirth, Psychological Well-Being and Pregnancy Outcomes in Primipara Women - Kakar, Zahida; Masih, Sarfraz; Mukhtar, Madiha (Journal of Neonatal Surgery, 2025)
Fear of childbirth is a common problem and has a negative impact on the childbirth experience. This fear causes birth to take longer, and the mother suffers labor pain more intensely. This study aims to explore the effects of interventions on the World Health Organization module on fear of childbirth, psychological well-being and pregnancy outcomes in primipara women. The data were collected from 80 primipara women who received treatment at the obstetrics division in Pishin Teaching Hospital in Balochistan. The study utilized separate instruments to assess the impact of antenatal nursing treatments on delivery anxiety, psychological well-being, and pregnancy outcomes in primipara women. The differences in the scores were assessed between pre- and post-intervention through the Mann-Whitney U test. Results showed that those participants were mainly young women from rural locations and housewives. Moreover, women's fear of childbirth reduced significantly; 48.8% no longer feared pregnancy, and almost 73% had intense birth fears initially (p-value<0.001). After the intervention, 76.3% of women showed very good mental health levels. The results show that 65% of women delivered their babies at normal times, and 30% went through C-sections. The findings show that early pregnant women's support from nurses lowers pregnancy fears, keeps mothers mentally strong, and helps babies and moms recover well after birth. Our results show why healthcare providers should add these helpful programs to normal prenatal visits